Sample Stratification with Non-Nested Alternatives: Theory and a Hedonic Example - Goodman, Allen C.; Dubin, Robin A. (The Review of Economics and Statistics, 1990)
Econometric analysis often addresses model misspecification due to the improper pooling of observations. One major problem in testing for improper pooling is the requirement that alternative stratifications be obtained from others through sets of restrictions (i.e., that they be nested stratifications), thus eliminating a large class of alternative non-nested stratifications. We propose that non-nested tests can be used to compare non-nested stratifications. We formally define the econometric problem, and show the applicability of the J, JA, Cox and non-nested F tests. We then use the four tests to compare spatial stratifications in a model of a house price determination. Copyright 1990 by MIT Press.